PWE-143 Development of Informatics Tools for The UK IBD Registry Using Routine Data: Profiling of National-Level Hospital Activity for IBD Patients in England. (17th August 2016) - Shawihdi, M; Osborne, A; Devonport, E; Driscoll, R; Cummings, F; Bloom, S; Williamson, P; Pearson, M; Bodger, K
Abstract : Introduction: We report a project to generate profiles of NHS activity for IBD patients receiving care in English hospitals, with national and local level activity reports (Trust and Primary Care Organisation) as the basis for clinically validated metrics to support services. Methods: COHORT : 352, 614 patients with a specific IBD diagnosis between 2003/4 and 2013/14. DATASETS: All-cause events for the cohort for each year from HES datasets: Admitted Patient Care (APC, daycase and inpatient care), Outpatient (OP ) and Accident & Emergency (A&E ). Source: Health & Social Care Information Centre. ANALYSIS: In IBM-SPSS, Excel and SAS. Clinical review of ICD-10 (diagnosis) and OPCS-4 (procedure) codes for all APC events, categorising all-cause activity into logical baskets of IBD-related primary diagnoses (e.g. perianal abscess) or procedures (e.g. colonoscopies). APC categorised as elective daycases (El-D ), admissions (El-Ad ) or emergencies (Em-Ad ). The OP dataset lacks diagnosis, so categorised by GI-relevant specialities. A&E contacts were all-cause (non-admitted). Data reported are 2013/14. Results: APC: 149, 115 IBD patients (42% of cohort) had hospital admission in 13/14 (389, 574 admissions; El-D, 246, 064; El-Ad, 26, 911; Em-Ad, 105, 482; Other, 11, 117). Of Em-Ad, the primary diagnosis code was IBD-specific in 17, 274 (CD: 10, 077; UC: 7, 197), non-specific IBD in 455, IBD-related conditions in 9, 709, relevant GI symptoms in 6, 934, benign anorectal conditions in 2, 445, anaemias in 1, 158, enteric infections in 1, 148, colonic or small bowel cancers in 472. Categorising Em-Ad by procedures identified 5, 515 with GI surgery (Perianal: 1, 233; Colonic or SB resection: 1, 547). Of El-Ad, 7, 030 included GI surgery . El-D included 70, 354 lower endoscopies and 73, 968 infusions/injections . Outpatient Activity : 244, 248 IBD patients (69% of cohort) attended clinic (1, 351, 807 all-cause visits), of which 387, 503 were gastroenterology or general surgery . A&E Activity: 98, 838 all-cause attendances for 53, 083 IBD patients (non-admitted). At organisation level (PCT), mean emergency bed days (primary IBD diagnosis) was 247 per 100, 000. Conclusion: Analysis of IBD-related hospital activity in routine data is possible but requires complex algorithms. Our candidate metrics at Trust and Primary Care Organisation level will be shared with front line teams, including links between A&E, OPD and APC events and refined iteratively. Linkage to IBD Registry dataset has been tested and will allow future enhancements. Disclosure of Interest: M. Shawihdi Grant/research support from: Crohn's & Coliitis UK, A. Osborne: None Declared, E. Devonport: None Declared, R. Driscoll Consultant for: AbbVie, F. Cummings: None Declared, S. Bloom: None Declared, P. Williamson: None Declared, M. Pearson: None Declared, K. Bodger Grant/research support from: Crohn's & Colitis UK, Speaker bureau with: AbbVie